Integrative analysis of copy number and gene expression data suggests novel pathogenetic mechanisms in primary myelofibrosis. Issue 7 (25th November 2015) - Salati, Simona; Zini, Roberta; Nuzzo, Simona; Guglielmelli, Paola; Pennucci, Valentina; Prudente, Zelia; Ruberti, Samantha; Rontauroli, Sebastiano; Norfo, Ruggiero; Bianchi, Elisa; Bogani, Costanza; Rotunno, Giada; et al.
Abstract : Primary myelofibrosis (PMF) is a Myeloproliferative Neoplasm (MPN) characterized by megakaryocyte hyperplasia, progressive bone marrow fibrosis, extramedullary hematopoiesis and transformation to Acute Myeloid Leukemia (AML). A number of phenotypic driver (JAK2, CALR, MPL) and additional subclonal mutations have been described in PMF, pointing to a complex genomic landscape. To discover novel genomic lesions that can contribute to disease phenotype and/or development, gene expression and copy number signals were integrated and several genomic abnormalities leading to a concordant alteration in gene expression levels were identified. In particular, copy number gain in the polyamine oxidase (PAOX) gene locus was accompanied by a coordinated transcriptional up‐regulation in PMF patients. PAOX inhibition resulted in rapid cell death of PMF progenitor cells, while sparing normal cells, suggesting that PAOX inhibition could represent a therapeutic strategy to selectively target PMF cells without affecting normal hematopoietic cells' survival. Moreover, copy number loss in the chromatin modifier HMGXB4 gene correlates with a concomitant transcriptional down‐regulation in PMF patients. Interestingly, silencing of HMGXB4 induces megakaryocyte differentiation, while inhibiting erythroid development, in human hematopoietic stem/progenitor cells. These results highlight a previously un‐reported, yet potentially interesting role of HMGXB4 in the hematopoietic system and suggest that genomic and transcriptional imbalances of HMGXB4 could contribute to the aberrant expansion of the megakaryocytic lineage that characterizes PMF patients. Abstract : What's new? Primary myelofibrosis (PMF) is a proliferative hematopoietic stem cell disorder associated in some cases with mutations in the JAK‐STAT signal transduction pathway. Here the authors performed a detailed genetic analysis of blood and bone marrow samples and identified the gain of function of the polyamine oxidase PAOX and the loss of function of the chromatin modifier HMGXB4 as novel genomic abnormalities in PMF. This brings new insight into the mechanism of PMF development as in vitro manipulations of the two factors affected resistance to apoptosis and hyperplastic megakaryopoiesis, both features of PMF.